SELECTION OF THE BEST SEM MODEL TO IDENTIFY FACTORS AFFECTING MARKETING PERFORMANCE IN THE ICT INDUSTRY - Hikmah, Zetil; Wijayanto, Hari; Aidi, Muhammad Nur (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2023)
The digital revolution in society and the advances in marketing practices create tremendous challenges for companies and even more so for Information and Communication Technology (ICT) service providers. They are faced with increasingly complex and rapidly changing market competition, knowing these problems can use SEM to form a research model and find out the relationship between latent variables and their indicators. The purpose of this study is to identify the best structural equation model that can describe Marketing Performance in the ICT Industry in Indonesia. The data used in this study is primary data obtained from the results of distributing offline and online questionnaires to 300 management levels working in the ICT Industry. The methods compared in this study are Covariance Based Structural Equation Modeling and Partial Least Square Structural Equation Modeling. The results showed that the best model to determine the factors that influence Marketing Performance in the ICT Industry in Indonesia is PLS-SEM with the goodness-of-fit model R2 for the latent variable Marketing Performance is 0.436. This shows that the accuracy of the variables CEM, DBI and DOE together in predicting MP variables is relatively weak. Based on the PLS-SEM model, it is found that Digital Operational Excellence is a mediator that can increase the influence of Customer Experience Management on Marketing Performance. Meanwhile, Digital Business Innovation has no significant effect in increasing the influence of Customer Experience Management on Marketing Performance. The novelty of this research is the development of the best SEM models (CB-SEM and PLS-SEM) in the field of Information and Communication Technology in Indonesia.